Implementasi Program Pembinaan Tahfidz melalui Metode Tikrar untuk Meningkatkan Kemampuan Menghafal pada Santri di Madrasah Diniyah Baitul Jannah Cisaat Kasomalang - Sri Wahyuningsih; Aep Saepudin; Iwan Sanusi (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research is motivated by the low interest of students in memorizing the Quran, the ease with which they forget the memorization that has been memorized, as well as the difficulty and lack of motivation in the memorization process. The purpose of this study is to examine the implementation of the tahfidz coaching program through the Tikrar method in improving students' memorization skills. This program is designed to help participants memorize the Quran Juz 30 systematically, structured, and sustainable, with various activities and methods that facilitate the process of memorizing, repeating, and understanding the contents of the Quran. This research departs from the idea that the Tikrar method can help students memorize Juz 30 accurately, pay attention to correct tajweed and makhraj, and maintain memorization consistently. In addition, students are also expected to understand the meaning of the memorized verses and be able to apply them in everyday life. The Tikrar method not only focuses on memorization, but also on understanding and practicing the teachings of the Qur'an. The results of the implementation of this tahfidz program at Madrasah Diniyah Baitul Jannah Cisaat Kasomalang show a significant increase in the students' memorization ability. Weekly evaluation and intensive repetition are proven to strengthen memorization and improve the quality of tajweed recitation. However, this program still faces challenges such as differences in memorization ability, time constraints, and psychological pressure. For this reason, further adjustments are needed so that this program can meet the needs of santri more effectively in the future. Abstrak. Penelitian ini dilatarbelakangi oleh rendahnya minat santri dalam menghafal Alquran, mudahnya mereka melupakan hafalan yang telah dihafal, serta kesulitan dan kurangnya motivasi dalam proses menghafal. Tujuan penelitian ini adalah untuk mengkaji implementasi program pembinaan tahfidz melalui metode Tikrar dalam meningkatkan kemampuan hafalan santri. Program ini dirancang untuk membantu peserta menghafal Alquran Juz 30 secara sistematis, terstruktur, dan berkelanjutan, dengan berbagai aktivitas dan metode yang memudahkan proses menghafal, mengulang, dan memahami isi Alquran. Penelitian ini berangkat dari pemikiran bahwa metode Tikrar dapat membantu santri menghafal Juz 30 dengan akurat, memperhatikan tajwid dan makhraj yang benar, serta mempertahankan hafalan secara konsisten. Selain itu, santri juga diharapkan memahami makna ayat-ayat yang dihafal dan mampu mengaplikasikannya dalam kehidupan sehari-hari. Metode Tikrar tidak hanya berfokus pada hafalan, tetapi juga pada pemahaman dan pengamalan ajaran Al-Qur'an. Hasil dari penerapan program tahfidz ini di Madrasah Diniyah Baitul Jannah Cisaat Kasomalang menunjukkan peningkatan yang signifikan dalam kemampuan hafalan santri. Evaluasi mingguan dan pengulangan intensif terbukti memperkuat hafalan dan meningkatkan kualitas bacaan tajwid. Namun, program ini masih menghadapi tantangan seperti perbedaan kemampuan hafalan, keterbatasan waktu, dan tekanan psikologis. Untuk itu, diperlukan penyesuaian lebih lanjut agar program ini dapat memenuhi kebutuhan santri secara lebih efektif di masa mendatang.